The Impact of E-commerce Tactics Using K-Pop Idol on Brand Awareness, Hedonic Shopping Motivation towards Purchase Intention among K-Pop Fans - Nabila Putri Andira; Raditya Aji Prasetyo (International Journal of Social Service and Research, 2023)
The use of K-Pop girlbands/boybands as endorsers is booming by Indonesian e-commerce. For this reason, this research aims to know what factors are owned by endorsers that can influence consumer purchase decisions for the products offered by e-commerces. The secondary motivation of this research is to obtain empirical data on how influential the tactics made by e-commerce using K-Pop girlband/boyband are on purchase intention. Impact of celebrity worship factors related to celebrity worship are Entertainment-Social, Intense-Personal, Borderline-Pathological. That's all under the moderating effect of risk was estimated from the perceptions of Indonesia's K-Pop Fans (n =100) using variance-based structural equation modeling and PLS-SEM process. There is a positive correlation between K-Pop Brand Ambassador to raise Brand Awareness, Hedonic Shopping Motivation towards Purchase Intention among K-Pop Fans. Limitation to get a number of respondents with a high purchase power. Contributes to the current knowledge-related online buying behavior in virtual retail formats and helps marketers in streamlining their focus in using celebrity endorsers to increase purchase decisions of targeted consumers.